Mythological stuff and literary gender: An example in Lope de Vega - Domínguez Caparrós, José (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Abstract not available.
Keywords: mythology; literary gender; Lope de Vega; Siglo de Oro